Genomic insights and antimicrobial resistance profiles of CRKP and non-CRKP isolates in a Beijing geriatric medical center: emphasizing the blaKPC-2 carrying high-risk clones and their spread - Ge, Xin; Zhou, Yu; Jin, Hang; Liu, Kangkang; Zhu, Kunpeng; Yu, Yulong; Xue, Jingzhuang; Wang, Qi; Du, Xinying; Wang, Hui; Xiang, Ying; Li, Wenjun; et al. (Frontiers in Microbiology, 2024)
The escalating resistance of Klebsiella pneumoniae, a prevalent pathogen in healthcare settings, especially its carbapenem-resistant K. pneumoniae (CRKP), to a wide array of antibiotics, notably β-lactams, constitutes a formidable challenge for healthcare and global public health management. This research compared the resistance phenotypes and genomic profiles of CRKP and Non-CRKP isolates in a Beijing hospital, focusing on high-risk blaKPC-2 gene-bearing CRKP clones and the structure of mobile genetic elements facilitating their spread across hospital departments. 40 K. pneumoniae isolates were collected from various departments of the hospital and subjected to antimicrobial susceptibility testing and whole-genome sequencing to analyze their resistance phenotypes and genomic features. The study revealed that Among the 31 CRKP isolates, ST11 is the most common sequence type, with K47 and OL101 being the dominant capsule types, primarily observed in the respiratory department. In terms of antimicrobial susceptibility: 87.5% of the isolates exhibited multidrug resistance (MDR), with a high resistance rate of 30% against tigecycline. All CRKP isolates demonstrated resistance to multiple drug classes (≥ 5 CLSI classes). Non-CRKP isolates also showed high resistance rates to minocycline and doxycycline (77.8%). the ST11-KL47-OL101 type emerged as the predominant clone among the CRKP isolates carrying the blaKPC-2 gene. This dominance appears to be mediated by the pKpnR03_2 plasmid, which harbors not only blaKPC-2 and rmtb but also gene clusters pertinent to iron transport and arsenic resistance. These isolates, clustering in the C3 clade of the phylogenetic tree, exhibited minor genetic variations and close evolutionary relationships, suggesting a plasmid-driven spread across various hospital departments. In summary, our study highlights the extensive spread of antibiotic-resistant K. pneumoniae across various departments in our hospital, with a particular emphasis on the dominant clonal proliferation of the ST11-KL47-OL101 CRKP strain. This finding underscores the significant role of plasmid-mediated gene transfer in the evolution and dissemination of resistant strains within hospital environments. The study emphasizes the necessity for ongoing surveillance of antibiotic resistance and genomic analysis in hospital settings to effectively monitor and manage these challenges.